2017
DOI: 10.1128/aac.02007-16
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Clinical Utility of an Absolute Procalcitonin Value for Predicting a Positive Culture Result

Abstract: Various procalcitonin ranges have been established to guide antimicrobial therapy; however, there are no data that establish whether the initial procalcitonin value can determine the likelihood of a positive culture result. This study aimed to establish if the initial procalcitonin value, on clinical presentation, has a positive predictive value for any positive culture result. This was a retrospective study of 813 medical intensive care unit patients. Data collected included patient demographics, procalcitoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…Discrimination for bacteremia is low in patients meeting systemic inflammatory response syndrome (SIRS) criteria or all-comers in the emergency department. (11)(12)(13)(14) Importantly, just as with blood cultures, these biomarker results may not be available at the time the clinician first suspects an infection. Molecular methods using polymerase chain reaction (PCR) to detect bacteremia and fungemia have higher accuracy than blood cultures or biomarker tests.…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination for bacteremia is low in patients meeting systemic inflammatory response syndrome (SIRS) criteria or all-comers in the emergency department. (11)(12)(13)(14) Importantly, just as with blood cultures, these biomarker results may not be available at the time the clinician first suspects an infection. Molecular methods using polymerase chain reaction (PCR) to detect bacteremia and fungemia have higher accuracy than blood cultures or biomarker tests.…”
Section: Introductionmentioning
confidence: 99%
“…That could explain our insignificant results. Finally, procalcitonin was recently identified as a novel predictive marker of bloodstream infection, although one study identified it as a poor predictor of culture positivity [25]. In our study, procalcitonin was not evaluated in most cases.…”
Section: Discussionmentioning
confidence: 66%
“…Several studies demonstrated that -for certain sources of sepsis (e.g., LRTIs), the frequency of bacteremia was lower than that of other sources (e.g., urinary tract infections) [21] -if compared with bacteremic patients, non-bacteremic septic patients were associated with lower serum levels of procalcitonin [12,13,[15][16][17].…”
Section: Source Of Infectionmentioning
confidence: 99%